Influence of water activity and temperature on the growth of Wallemia sebi: Application of a predictive model - Patriarca, Andrea Rosana (2001)
Germination and growth of Wallemia sebi were examined on media of aw adjusted with glycerol in the range of 0.96-0.77, at 25°C and 30°C. The effect of temperature on the germination time was significant except between 0.95 and 0.88aw. At low aw levels as well as above 0.95, the increase of temperature produced an increment in the germination time. The minimum aw for germination was also affected by temperature, being lower at 25°C (0.80 aw) than at 30°C (0.82 aw). Radial growth rates at 25°C were higher than at 30°C. The optimum aw value for growth of W. sebi was 0.94 at both temperatures. The minimum aw for growth was higher than minimum for germination and was also dependent on temperature (0.84 at 25°C and 0.86 at 30°C). An empirical mathematical model was fitted to the measured growth data, providing a good approach to the description of the effect of aw on the radial growth rate of W. sebi.